DZIELIMY SIĘ DOŚWIADCZENIEMUrinary bladder outlet obstruction post renal artery stenting – a case of hyperperfusion syndrome? - Duszańska, Agata; Świątkowski, Andrzej; Głowacki, Jan; Świerad, Marcin; Kalarus, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
We report a case of urinary bladder outlet obstruction post successful renal artery stenting (RAS). A 28-year old hypertensive man with left renal artery stenosis was referred for an elective RAS. Renal artery angiogram confirmed subtotal left artery occlusion. RAS was performed without any initial complications. Two hours after RAS the patient developed left-sided pain followed by haematuria and then anuria. Urgent abdominal ultrasound scan showed urinary bladder filled with thrombotic masses and no signs of renal artery rupture and retroperitoneal haemorrhage. Obstruction of the bladder was released by mechanical maneuvering with Foley catheter and washing out the bladder with saline. Conclusions: Severe haematuria resulting in urinary tract blockage may complicate renal artery stenting. The most likely explanation for such a complication is hyperperfusion phenomenon. Further studies are warranted to establish the incidence, risk factors and postprocedural treatment standards of such complication.